Evaluation of SIMRAL with CIPP Model on the Performance of State Civil Apparatus (ASN): Department of Public Works and Spatial Planning (PUPR) Kota Bogor - Yuliati, Ety; Ramly, Amir Tengku; Ayuniyyah, Qurroh (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2024)
SIMRAL is used to manage APBD (Regional Government Budget), planning, budgeting, implementation, reporting, accountability, and audit supervision. Therefore, its series is long and unbroken. This study evaluates SIMRAL's effect on the performance of civil servants in the PUPR (Public Works and Spatial Planning) office of Bogor City to achieve performance at the individual, unit, or organisational level. The objective of this study is to evaluate the effectiveness of SIMRAL usage and the performance of civil servants in the PUPR office of Bogor City. The research method used is a mixed-method approach, with an evaluative program/policy approach using the CIPP model. This method focuses on evaluating four main components: (1) SIMRAL usage policy and objectives, (2) human resource quality, (3) SIMRAL application process, and (4) the output and outcome of SIMRAL usage. The output of this research is a policy recommendation on using SIMRAL, considering the mayor's regulations, work effectiveness-efficiency, human resource performance competency, service quality, budget control, and proper decision-making. SIMRAL also continuously enhances work motivation and quality.